The Energy Level Alignment at the Buffer/Cu(In,Ga)Se2 Thin-Film Solar Cell Interface for CdS and GaOx - Valenta, Donald; Yetkin, Hasan Arif; Kodalle, Tim; Bombsch, Jakob; Garcia-Diez, Raul; Hartmann, Claudia; Ueda, Shigenori; Félix, Roberto; Frisch, Johannes; Bodenstein-Dresler, Lucas; Wilks, Regan G.; Kaufmann, Christian A.; et al. (Advanced Materials Interfaces, 2024)
Sputter-deposited GaOx (i.e., oxygen-deficient gallium oxide) films are evaluated as a potential replacement for the standard CdS buffer layers in Cu(In,Ga)Se2 (CIGSe) based thin-film photovoltaics. The energy level alignment at the GaOx/CIGSe and CdS/CIGSe interfaces are compared by means of direct and inverse photoemission. For the GaOx/CIGSe a (0.04 ± 0.07) eV (i.e., a small spike-like) conduction band offset (CBO) and a (−3.21 ± 0.19) eV (i.e., a large cliff-like) valence band offset (VBO) are found, which suggests a nearly ideal charge-selective contact. The derived GaOx band gap of (4.80 ± 0.25) eV confirms its utility as a highly transparent buffer layer. However, the GaOx (with x derived to be 1.1 ± 0.1) exhibits considerable (presumably) defect-related occupied states above the valence band maximum. It is proposed that these states may increase charge carrier recombination and decrease open circuit voltage in respective devices; also explaining why solar cells with standard CdS buffer outperform devices with GaOx buffer, despite less ideal electronic interface properties (CBO: (−0.18 ± 0.07) eV, VBO: (−0.98 ± 0.15) eV) and the smaller CdS band gap of (2.35 ± 0.22) eV.
CRIS-Team Scopus Importer:2024-03-15
Keywords: CdS buffer; chalcopyrite thin-film solar cell; energy level alignment; GaO; interface properties